Acute compartment syndrome of the thigh in a high school soccer player - Golden, D. W.; Flik, K. R.; Turner, D. A.; Bach, B. R.; Sawyer, J. R. (The Physician and Sportsmedicine, 2005)
Compartment syndrome in the lower leg, most commonly related to exertion, has been well documented in athletes. However, compartment syndrome resulting from trauma is rare in athletes, as in this case of a 17-year-old male goalie who sustained a direct blow to his thigh during a soccer game. He was successfully treated with early fasciotomy and delayed wound closure, and he made a full recovery.